Foreign Direct Investment Restrictions: Legal Aspects in the Context of Eurasian Integration - L. V. Tsareva (Евразийская интеграция: экономика, право, политика, 2021)
The article outlines current trends in the legal regulation of foreign direct investment; analyzes the current approaches of EAEU member states to the restriction of foreign investment; systematizes the provisions of the Union law, which affect the adoption and application of national measures to restrict and control foreign direct investment; identifies the conceptual differences between EAEU law and EU law in regulating freedom of establishment. The aim of the research is to determine the degree of the EAEU law influence on the introduction by member states of restrictive measures against direct investment from member states. The author concludes that the legal framework for national measures to restrict FDI from member states is predetermined by the norms of the Union law on ensuring freedom of establishment as a form of investment, operated with individual and general exceptions, that allow to take the measures necessary to protect the national priority interests.